2009
DOI: 10.1016/j.nlm.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Habituation to repeated stress: Get used to it

Abstract: Habituation, as described in the landmark paper by Thompson and Spencer (1966), is a form of simple, nonassociative learning in which the magnitude of the response to a specific stimulus decreases with repeated exposure to that stimulus. A variety of neuronal and behavioral responses have been shown to be subject to habituation based on the criteria presented in that paper. It has been known for several decades that the magnitude of hypothalamic-pituitary-adrenal (HPA) activation occurring in response to a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
301
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(339 citation statements)
references
References 82 publications
(139 reference statements)
22
301
1
4
Order By: Relevance
“…1,31 The cerebral-network hypothesis is largely based on findings from functional neuroimaging in humans during hypoglycemia, 43,44 particularly [ 15 O]water PET measurements of regional cerebral blood flow as an index of regional brain synaptic activity, 31,75,76 and the psychophysiological concept of habituation of the response to a given stress and its proposed mechanism. 77 The posterior paraventricular nucleus of the thalamus is a brain site at which previous stress, such as stress induced by restraint, acts to attenuate responses to subsequent episodes of that stress in rats. 78 Lesions in the posterior paraventricular nucleus of the thalamus block habituation of the hypothalamic-pituitaryadrenocortical response to repeated restraint.…”
Section: Brain-metabolism Hypothesismentioning
confidence: 99%
“…1,31 The cerebral-network hypothesis is largely based on findings from functional neuroimaging in humans during hypoglycemia, 43,44 particularly [ 15 O]water PET measurements of regional cerebral blood flow as an index of regional brain synaptic activity, 31,75,76 and the psychophysiological concept of habituation of the response to a given stress and its proposed mechanism. 77 The posterior paraventricular nucleus of the thalamus is a brain site at which previous stress, such as stress induced by restraint, acts to attenuate responses to subsequent episodes of that stress in rats. 78 Lesions in the posterior paraventricular nucleus of the thalamus block habituation of the hypothalamic-pituitaryadrenocortical response to repeated restraint.…”
Section: Brain-metabolism Hypothesismentioning
confidence: 99%
“…On subsequent exposures, this response may either increase or decrease. Habituation is the process whereby a response gradually reduces with repeated presentation of the eliciting stimulus, and the threshold increases (Grissom and Bhatnagar, 2009). In contrast, sensitization is the process whereby an animal's response increases on presentation of a stimulus (Davis,1974).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of many of these challenges have been studied, albeit mostly as a single stressor (Barton and Peter, 1982;Gorissen et al, 2012;Di Marco et al, 2008;Pottinger, 2010;Remen et al, 2012). Studies on mammals (Aguilera and Rabadan-Diehl, 2000;Dhabhar and McEwen, 1997;Grissom and Bhatnagar, 2009;Thorsell et al, 1999), as well as fish (Schreck, 2000), show they have great resilience to a single stressor given repeatedly over long periods of time; however, knowledge on how ectotherms respond to multiple persistent stressors is very scant. One study on Atlantic salmon (Salmo salar, L.) has shown that chronic stress followed by an additional maze challenge resulted in a suppressed cortisol response, and decreased neural plasticity and learning ability (Grassie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%